Bank mergers and the dynamics of deposit interest rates - Ben R. Craig; Valeriya Dinger (Deutsche Bundesbank, 2008)
Despite extensive research interest in the last decade, the banking literature has not reached a consensus on the impact of bank mergers on deposit rates. In particular, results on the dynamics of deposit rates surrounding bank mergers vary substantially across studies. In this paper, we aim for a comprehensive empirical analysis of a bank merger's impact on deposit rate dynamics. We base the analysis on a unique dataset comprising deposit rates of 624 US banks with a monthly frequency for the time period 1997-2006. These data are matched with individual bank and local market characteristics and the complete list of bank mergers in the US. The data allow us to track the dynamics of bank mergers while controlling for the rigidity of the deposit rates and for a range of merger, bank and local market features. An innovation of our work is the introduction of an econometric approach of estimating the change of the deposit rates given their rigidity.
Keywords: L11; G21; 330; Deposit rate dynamics; bank mergers; deposit rate rigidity; Bank; Fusion; Einlagengeschäft; Zins; Struktur-Performance-Modell; USA